Swyer-James-MacLeod Syndrome: a rare case - Singal, Kiran Kumar; Bhatti, Karun Puran; Gupta, Abhinav; Gupta, Nitin; Samra, Ravneet; Gautam, Sumit (Bangladesh Journal of Medical Science, 2015)
This case report describes a patient with Swyer-James-MacLeod Syndrome (SJMS) in an adult female diagnosed on the basis of findings on X-ray chest, high resolution CT (HRCT) of chest. This rare syndrome is considered to be an acquired disease due to repeated pneumonias in early childhood. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.402-404